On Dialactic Assessment of Professional Experience of Law Enforcement in the Field of Law Enforcement - Vladimir Valentinovich Kozhevnikov (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This scientific article is devoted to the problem of professional experience of law enforcement in the law enforcement sphere. The author emphasizes that the latter is not only positive in nature, contributing to a quick and correct assessment, legal qualification of a particular situation, but also negative, causing professional deformation of the subjects of the application of law.